1999
DOI: 10.1001/jama.281.21.1991
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Preferences for Neonatal Outcomes Among Health Care Professionals, Parents, and Adolescents

Abstract: When asked to rate the health-related quality of life for the hypothetical conditions of children, health care professionals tend to provide lower utility scores than do adolescents and their parents. These findings have implications for decision making in the neonatal intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
196
4
6

Year Published

2000
2000
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 325 publications
(213 citation statements)
references
References 32 publications
7
196
4
6
Order By: Relevance
“…This change of internal standards or “response‐shift”41 is not represented in the HUI. In the majority of patients, the responses were generated by parents and health professionals, who tend to provide lower valuations for HRQL than patients,39, 42, 43 suggesting that the discrepancy between HRQL as perceived by patients and as perceived by society may even be greater. No agreement exists on how to do justice to both the objective function and the subjective judgment of HRQL.…”
Section: Discussionmentioning
confidence: 99%
“…This change of internal standards or “response‐shift”41 is not represented in the HUI. In the majority of patients, the responses were generated by parents and health professionals, who tend to provide lower valuations for HRQL than patients,39, 42, 43 suggesting that the discrepancy between HRQL as perceived by patients and as perceived by society may even be greater. No agreement exists on how to do justice to both the objective function and the subjective judgment of HRQL.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of whose values to use to generate the scoring algorithms for generic preference based instruments applicable for young people may have important policy implications because there is evidence to indicate that adults' preferences for identical health states may differ from adolescents' preferences (Ratcliffe et al, 2015b;Ratcliffe et al, 2012b;Norquist et al, 2008;Saigal et al, 1999) In an empirical comparison of adult versus adolescent specific scoring algorithms for the CHU9D and the AQoL-6D Adolescent, Ratcliffe et al (2012b) found notable differences. For the CHU9D instrument, employment of the adolescent algorithms resulted in lower mean health state values than the adult algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…15 In addition, there is a tendency to emphasize objective measures, deficits and impairments rather than more subjective humanistic values. 16 It is clear that those providing counseling must be well trained, aware of their own inherent biases and willing and able to impart a variety of viewpoints and provide ready access to a wide spectrum of information sources.…”
Section: Volume 34 No 4 -November 2007mentioning
confidence: 99%